2018
DOI: 10.1016/j.neo.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Dual BRD4 and AURKA Inhibition Is Synergistic against MYCN-Amplified and Nonamplified Neuroblastoma

Abstract: A majority of cases of high-risk neuroblastoma, an embryonal childhood cancer, are driven by MYC or MYCN-driven oncogenic signaling. While considered to be directly “undruggable” therapeutically, MYC and MYCN can be repressed transcriptionally by inhibition of Bromodomain-containing protein 4 (BRD4) or destabilized posttranslationally by inhibition of Aurora Kinase A (AURKA). Preclinical and early-phase clinical studies of BRD4 and AURKA inhibitors, however, show limited efficacy against neuroblastoma when use… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 61 publications
(71 reference statements)
0
19
0
Order By: Relevance
“…The BET inhibitor BMS-986158 is currently under clinical trial in pediatric cancer, including neuroblastoma (NCT03936465). Furthermore, some studies described a combination therapy of BETi with other drugs has a synergistic effect against NB tumor progression (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…The BET inhibitor BMS-986158 is currently under clinical trial in pediatric cancer, including neuroblastoma (NCT03936465). Furthermore, some studies described a combination therapy of BETi with other drugs has a synergistic effect against NB tumor progression (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…As BET inhibition was shown to be synergistic with Aurora A inhibition in neuroblastoma cells 29 , we hypothesized that we could potentiate the effects of JQ1 on GBM cells by combining it with MLN8237. Similar to Felgenhauer et al 29 where they found synergism between BET and Aurora A inhibitors irrespective of MYCN status of neuroblastoma cells, we could demonstrate a strong synergism in all four tested GBM cell lines, irrespective of whether they had high (JQ1-sensitive) or low (JQ1-resistant) MYCN expression (Fig. 5d).…”
Section: Resultsmentioning
confidence: 99%
“…It does appear that the inhibition of the epigenetic regulator BRD-4 is not the mechanism by which MP1 inhibits MYCN given the lack of effect on gene or protein expression. This is an important observation given the early clinical use of BRD-4 inhibitors in MYCN amplified NB [22].…”
Section: Discussionmentioning
confidence: 99%